A dancer, a groomer, a folk artist and a viola player - case reports of occupational musculoskeletal and peripheral nervous system diseases - Monika Najder-Gawlik; Marta Wiszniewska; Agnieszka Lipińska-Ojrzanowska (Nofer Institute of Occupational Medicine, 2022)
Work-related diseases of the musculoskeletal and the peripheral nervous system are classified as overload cumulative microtrauma diseases, resulting from chronic overload and/or damage of specific neuromusculoskeletal structures. Occupational activities which predispose to them are characterised by monotypy (repetition of movements during a significant part of the working shift). Authors described 4 cases of women with musculoskeletal and peripheral nervous system disorders qualified as occupational background just in the 2nd instance of medical certification. Detailed analysis of occupational exposure and medical interview with individual diagnostic approach allowed to determine the occupational etiology of diseases, regardless of non-occupational risk factors in some cases, even if the workstation was not common. Difficulties in estimating the probability of disease process induction on the background of occupational exposure are caused by frequent coexistence of non-occupational risk factors. The 2-tier system of certification provides an independent evaluation of medical history and occupational exposure. Med Pr. 2022;73(1):71-8